IMPLEMENTASI LAYANAN BK DALAM MENINGKATKAN PERKEMBANGAN SOSIAL-EMOSIONAL ANAK USIA DINI - ayu, inka (Edukids: Jurnal Pertumbuhan, Perkembangan, dan Pendidikan Anak Usia Dini, 2024)
The research investigates how counselling helps young children’s social-emotional development. Young children experience many social and emotional interactions that shape their future character and abilities. Counseling guidance is essential to help children develop good social skills, build positive relationships, and manage their emotions. One of the teachers of PAUD Aisyiyyah Pabelan was directly observed and thoroughly interviewed in this study, which used a qualitative approach. The result show that this kind of programme can be implemented in various early chilhood education institutions.